The Comparison of Brain Cognition Function between Active and Inactive Elderlies Male in Nursing Home (A Case-control Study in Tehran) - Anahita Khodabakhshi Koolaee; Saeid Sabz; Hossein Shahdadi; Farima Mohamadi (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objectives: Elderly is challenging period of lifespan. Old people need more care during this time and paying attention to their needs is a social responsibility. Insuffiiency in their cognitive function of the brain is as common problems in this living period. Therefore, the aim of current research is to determine the difference between active and inactive elderly in the cognitive function of the brain. Material and Methods: The current study is Ex-post with causal-comparative design. The population of the study was included all active and inactive elderly nursing home residents in the 6th district of Tehran that 60 active and 60 inactive elderly with voluntary sampling method were selected. The research instruments were Sharkey Physical Activity Index and Mini Mental State Examination. Statistical analysis conducted by independent t test and SPSS-22. Results: The mean (SD) of the cognitive function score in two groups of active and inactive elderly was respectively 21.7 (3), 10.2 (1.8) (P<0.001) and orientation, memory 12.4 (2.3), 10.9 (2.2) (P<0.001), attention and focus 3.4 (1.4), 2.9 (1.1) (P=0.35), assessment of language ability 5.9 (1.8), 4.6 (1.7) (P<0.001) and visualspatial abilities 0.8 (0.4), 0.6 (0.5) (P=0.004). Conclusion: The study showed that physical activity was effective in cognitive function of elderly. Hence, this method could be considered by counselors and mental health professionals in nursing homes and retirement centers, as a treatment approach to existing therapies.